Imperfect Quantum Photonic Neural Networks. Issue 3 (29th January 2023) - Ewaniuk, Jacob; Carolan, Jacques; Shastri, Bhavin J.; Rotenberg, Nir
Abstract: Quantum photonic neural networks are variational photonic circuits that can be trained to implement high‐fidelity quantum operations. However, work‐to‐date has assumed idealized components, including a perfect π Kerr nonlinearity. This work investigates the limitations of non‐ideal quantum photonic neural networks that suffer from fabrication imperfections leading to unbalanced photon loss and imperfect routing, and weak nonlinearities, showing that they can learn to overcome most of these errors. Using the example of a Bell‐state analyzer, the results demonstrate that there is an optimal network size, which balances imperfections versus the ability to compensate for lacking nonlinearities. With a sub‐optimal π / 10 π /10 effective Kerr nonlinearity, it is shown that a network fabricated with current state‐of‐the‐art processes can achieve an unconditional fidelity of 0.905 that increases to 0.999999 if it is possible to precondition success on the detection of a photon in each logical photonic qubit. These results provide a guide to the construction of viable, brain‐inspired quantum photonic devices for emerging quantum technologies. Abstract : Quantum photonic neural networks are brain‐inspired, reconfigurable nonlinear photonic circuits that can be taught to tackle many of the outstanding challenges of emerging quantum technologies. While previous proposals of these networks were idealized, this work unravels the intricate relationship between photon loss, optical nonlinearities, and network size, thus providing a guide to their optimal design in an experimentally viable setting.